South Africa : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper discusses the policy response by a sample of central banks to the ongoing oil and food price shocks in South Africa, drawing some lessons, which can help put in context developments in the country. The paper discusses first- and second-round effects of 'supply shocks,' and attempts to gauge second-round effects in South Africa. The paper also analyzes the factors that have constrained South Africa's growth since the end of apartheid, by comparing its GDP components and its saving and investment performance with those of a panel of faster-growing countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet